KARDIOCHIRURGIA DOROSŁYCHCoronary artery bypass grafting with carotid artery endarterectomy – does combined approach places a patient at greater risk of hemorrhagic complications than an isolated procedure? - Rachwalik, Maciej; Marczak, Jakub; Płonek, Tomasz; Barć, Piotr; Dorobisz, Andrzej; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: The appropriate management of patients with concomitant coronary and carotid vascular disease remains a subject of evaluation. The purpose of presented study was to compare hemostatic status and range of hemorrhagic complications following an isolated coronary revascularization and combined procedure of coronary artery bypass grafting with concomitant carotid artery endarterectomy. Material and Methods: Records of 60 patients were analyzed retrospectively. Two groups were elected; first – A consisted of patients undergoing CABG and CAE as a concurrent procedure and the second one of those treated with CABG alone – B. Presented study compares various values of hemostasis and blood loss parameters on four different stages of hospitalization. Results: Patients undergoing concomitant procedure presented with greater hemorrhagic complications mainly in the first postoperative day : total chest tube drainage was higher in Group A (1183 ml ±1223 ml vs. 888 ±529; p = 0.23), as was a total number of Red Blood Cells units used in treatment of postoperative anemia (2.57 ±3.23 vs. 1.77 ±1.33); APTT (39.1 seconds ±7.6 vs. 34.5 seconds ±9.1; p < 0.001); Pt (59 µg/ml ±9 vs. 80 µg/ml ±10; p < 0.001); and Hgb (9.8 g/dl ±0.8 vs. 10.8 g/dl ±1.3; p < 0.001). There was no difference in consumption of red blood cells units among the groups. Conclusions: We conclude as follows: 1. Hemorrhagic complications following simultaneous revascularization present at the greatest intensity during the first postoperative day. 2. Combined procedure should be regarded as a relatively safe tool in management of patients at risk of life – threatening vascular episode.